Parasites of Cambeva davisi (Siluriformes: Trichomycteridae) from the Cascavel stream, Neotropical area - Parra, Alini Beloto [UNESP]; Ramos, Igor Paiva [UNESP]; Delariva, Rosilene Luciana; de Arruda Amorim, João Paulo; Sereia, Diesse Aparecida de Oliveira; da Silva, Reinaldo José [UNESP]; Franceschini, Lidiane [UNESP] (Springer Nature, 2020)
The aim of the present study was to record the occurrence of parasites in Cambeva davisi (= Trichomycterus davisi) (Siluriformes: Trichomycteridae) from the Cascavel Stream, in the Iguaçu River basin, municipality of Cascavel, state of Paraná, Brazil, and present a review of the parasites reported infecting trichomycterids belonging to Cambeva and Trichomycterus species from the Neotropical region. Eighty-one fish specimens were collected using the electrofishing technique, with three standardized passes with a duration of 40 min, with extensions of 50 m for each site. In the laboratory, the fish were necropsied, and parasitological and histological analyses were conducted. Two parasite species were found and identified as nymphs of Sebekia oxycephala (Pentastomida) (Prevalence [P] = 8.54%) and Minilernaea floricapitella (Crustacea: Lernaeidae) (P = 1.23%), both representing new records of distribution and host-parasite relationships for genus Cambeva. The presence of the nymphs of S. oxycephala did not result in harmful histological changes or a significant inflammatory process in infected organs. Twenty-one taxa of parasites have been described parasitizing trichomycterids belonging to Trichomycterus (sensu stricto) and Cambeva from the Neotropical region. Nymphs of S. oxycephala have already been reported in freshwater fish belonging to 10 different orders, and M. floricapitella has been found parasitizing Brazilian fishes belonging to two orders. The nymphs of S. oxycephala did not cause histopathological changes and the new records of distribution and host-parasite relationships reported here enrich knowledge of the parasitic fauna of freshwater fish from the Neotropical region.
Keywords: Iguaçu River basin; Lernaeidae; Minilernaea floricapitella; Pentastomida; Sebekia oxycephala